1995
DOI: 10.1016/s0266-7681(05)80120-2
|View full text |Cite
|
Sign up to set email alerts
|

A Cadaver Study of the Effects of Dorsal Angulation and Shortening of the Metacarpal Shaft on the Extension and Flexion Force Ratios of the Index and Little Fingers

Abstract: Two experiments were performed on the second and fifth metacarpals of five normal cadaver hands. The forces obtained on full extension and flexion of the digits were measured. An oblique osteotomy was performed on the shaft of the metacarpal and fixed with dorsal angulation. The forces obtained on extension and flexion of the digits were measured. The relationships between the changes in force and the angle were analyzed. Flexion force decreased and extension force increased as the dorsal angulation increased,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 3 publications
1
57
0
2
Order By: Relevance
“…IJBR (2018) 09 (05) www.ssjournals.com [1,42] A closed reduction of displaced metacarpal neck fracture is reported to be difficult to achieve and impossible to retain in reduced position by non operative methods. By closed means using plaster splints, three point fixation cannot be achieved.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…IJBR (2018) 09 (05) www.ssjournals.com [1,42] A closed reduction of displaced metacarpal neck fracture is reported to be difficult to achieve and impossible to retain in reduced position by non operative methods. By closed means using plaster splints, three point fixation cannot be achieved.…”
Section: Surgical Techniquementioning
confidence: 99%
“…[2][3][4][5] While there is universal agreement over the management of undisplaced fractures by non-operative means, a varied opinion exists regarding the amount of acceptable volar angulation for non-operative management. [2][3][4][5][6][7][8][9]17,22,27,32,38,[41][42][43][44][45] Various reports suggest that it is almost impossible to maintain the reduction by non-operative means. [7,9,20,21,28,37,43,46] This leads to persistent deformity and morbidity in almost every case of displaced fifth metacarpal neck fracture treated non-operatively.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these fractures can be treated conservatively with an intrinsic plus position cast. Surgical treatment is indicated for unstable fractures, large dislocations or shortenings, as well as malrotations and communitive fractures [2].…”
Section: Introductionmentioning
confidence: 99%
“…Spiral metacarpal fractures commonly result in some shortening of the metacarpal shaft (9), which may subsequently cause extension lag at the metacarpophalangeal (MCP) joint and reduced grip strength (9-13). Several studies have documented the relationship between shortening and hand function (1,9,12,(14)(15)(16)(17)(18)(19)(20)(21), although the maximum amount of shortening that occurs following metacarpal fracture and acceptable limits appear to be controversial.Historically, spiral fractures occurring without scissoring have been treated surgically to restore metacarpal length and prevent these losses in power and function. Although previous studies have demonstrated beneficial outcomes in hand function following operative treatment of spiral metacarpal fractures (5,18,(22)(23)(24)(25)(26)(27)(28), surgical management is not without consequences and complications (27-31).…”
mentioning
confidence: 99%
“…Spiral metacarpal fractures commonly result in some shortening of the metacarpal shaft (9), which may subsequently cause extension lag at the metacarpophalangeal (MCP) joint and reduced grip strength (9-13). Several studies have documented the relationship between shortening and hand function (1,9,12,(14)(15)(16)(17)(18)(19)(20)(21), although the maximum amount of shortening that occurs following metacarpal fracture and acceptable limits appear to be controversial.…”
mentioning
confidence: 99%